'Listen to them': Adolescents' views on helping young people who self‐injure. Issue 5 (13th August 2013) - Berger, Emily; Hasking, Penelope; Martin, Graham
ABSTRACT: Non‐suicidal self‐injury (NSSI) among adolescents is a significant problem, yet the majority do not seek professional help. Parents and teachers are arguably most in contact with young people, and are critical in identifying and referring adolescent self‐injurers. This study explored what adolescents believe parents and teachers can do to help young people who self‐injure. A school‐based sample of 2637 students (aged 12–18 years) completed a self‐report questionnaire. Adolescents believe having non‐judgemental parents and teachers to talk to, improved parent–child relationships, referral to professionals, reduced school pressures, and student education, are pivotal to helping young self‐injurers. However, many adolescents, particularly those exposed to NSSI, were unsure about whether parents and teachers could do anything to help. These finding have important implications for educational programs that prepare parents and teachers to address adolescent NSSI.